Kajian Terhadap Pembagian Harta Warisan Tanah Dati Ditinjau Dari Hukum Islam Dan Hukum Adat - Siti Rizkiyani Salsabila Palembang; Adonia Ivone Laturette; Barzah Latupono (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Land has a very important position in customary law communities.Purposes of the Research: The purpose of this study is to find out and explain the distribution of inheritance on land based on Islamic law and customary law. Methods of the Research: The method used in this study is a normative juridical method with a statutory approach, a conceptual approach and a case approach. The legal materials used are primary, secondary and tertiary legal materials. The legal material is analyzed qualitatively in order to answer the problems studied.Results of the Research: Based on the results of the study, it shows that based on the provisions in Islamic inheritance law, all legal heirs have the right to inherit according to their respective portions or calculations so that regarding the distribution of inheritance land from dati is not prohibited and can be divided among legitimate heirs. However, it is different from customary law. It is clearly specified in the customary law inheritance system that the name of the land is communal so that it cannot be divided or divided. Therefore, the judge in the decision number of the Supreme Court Decision Number 2290 K/PDT/2003 which strengthened the previous decisions which basically stated that the distribution of the inheritance of dati land to the existing heirs, according to the author, if it is based on the Islamic inheritance law system, it is permissible. However, if it refers to the provisions of the customary inheritance law system, it is not allowed to divide the inheritance of the land to each heir.